1975
DOI: 10.1136/jnnp.38.9.865
|View full text |Cite
|
Sign up to set email alerts
|

Fibre function and perception during cutaneous nerve block.

Abstract: SYNOPSISIn awake human subjects, neural responses in radial nerves to electrical stimulation were recorded with intrafascicular tungsten microelectrodes. Changes in the activity of individual fibre groups during blocking procedures were recorded and correlated with simultaneous alterations in the perception of standardized stimuli. Light touch sensibility in hairy skin appeared to depend on the integrity of A-beta-gamma fibres, cold and pinprick on A-delta fibres, and warmth and dull pain on C fibres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
132
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(142 citation statements)
references
References 24 publications
(28 reference statements)
4
132
2
Order By: Relevance
“…burning upon extreme cooling), as well as to numerous masking mechanisms between A-and C-fibers (e.g. artificially reducing cold sensitivity in humans via anesthesia or compression ischemia, results innocuous skin cooling evoking burning sensations) (61,203,310). Interestingly, recent evidence in mice models of cold sensation has shown that C-fibers seems to predominantly contribute to conscious cold sensations in this animal (213).…”
Section: Peripheral Thermo-receptive Nerve Fibersmentioning
confidence: 99%
“…burning upon extreme cooling), as well as to numerous masking mechanisms between A-and C-fibers (e.g. artificially reducing cold sensitivity in humans via anesthesia or compression ischemia, results innocuous skin cooling evoking burning sensations) (61,203,310). Interestingly, recent evidence in mice models of cold sensation has shown that C-fibers seems to predominantly contribute to conscious cold sensations in this animal (213).…”
Section: Peripheral Thermo-receptive Nerve Fibersmentioning
confidence: 99%
“…C-fiber nociceptors have also been implicated in sensitivity to innocuous temperature (12)(13)(14). We therefore also asked whether PLC␤3-deficient mice could discriminate between 2 innocuous temperatures (30 vs. 40°C).…”
Section: Behavioral Responses To Innocuous or Noxious Thermal Mechanmentioning
confidence: 99%
“…From 1975 to 1990, Mackenzie and several other investigators provided a key insight into the neural basis of thermal reception and perception (20)(21)(22)(23). They found that a blockage of myelinated fibers (A-fibers) by ischemia or compression allows cold stimuli to activate non-myelinated C-fibers and to evoke heat or burning sensations.…”
Section: Introductionmentioning
confidence: 99%
“…According to this model, when the skin is stimulated by noxious cold temperatures, both C2 fibers and CMHC fibers will be activated, leading to pain sensation ( Figure 2B). Since cold stimuli evoke a hot or burning pain sensation following a blockage of A-fibers (20)(21)(22)(23), the cold quality of cold pain may be either encoded by an unknown population of myelinated nociceptors that respond to noxious cold or encoded by a transient activation of Aδ-cold fibers ( Figure 2B). Inactivation of Aδ-cold fibers at noxious cold temperatures (18) also removes cold-induced pain inhibition, which in turn allows more C2 fibers to activate the pain pathway.…”
Section: Introductionmentioning
confidence: 99%